PENGARUH PENAMBAHAN TEPUNG DAUN JAMBU BIJI DAN ARANG AKTIF PADA RANSUM PUYUH PETELUR (Coturnix coturnix japonica) TERHADAP PRODUKTIFITAS MASA PUNCAK PRODUKSI - Intan Dwi Rahayu (Universitas Islam Balitar, 2023)
This study aims to determine the effect of adding guava leaf flour and activated charcoal to laying quail rations on productivity during peak production. The method used was experimental with a factorial complete randomized design, consisting of 4 treatments and repeated 6 times, treatment variations of two factors guava leaf flour (JB) and activated charcoal (AA) namely, P0 (100% control feed), P1 ( P0 + 0.5% JB + 0.5% AA), P2 (P0 + 0.5% JB + 1.0% AA), P3 (P0 +1.0% JB + 0.5% AA). The material used was 240 laying quails aged 90 days. Variables observed included feed consumption, egg production and FCR. The results of this study showed that the addition of guava leaf flour and activated charcoal to laying quail rations during peak production had no significant effect (P<0.05) on feed consumption with the lowest number at P0, namely 25.01 gram/head/day, egg production the highest was at P1 which was 92.36% and the lowest FCR was at P1 which was 2.47. The conclusion of the addition of guava leaf meal and activated charcoal to laying quail rations on peak production productivity had no significant effect on feed consumption, egg production and FCR.